Effects of footwear and running speed on foot kinematics in the frontal plane - Meinert, I.; Bichler, S.; Brown, N.; Alt, W. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Excessive foot motion and increased running speed are frequently discussed as injury inducing factors in runners. We assessed foot kinematics using an inertial measurement unit while subjects ran at different running speeds wearing varying shoes. 20 male runners ran at 2.9, 3.5, 4.2 m/s wearing an all-purpose shoe (NS) and two differently configured running shoes: high arch support, wedges, soft damping (Con1) and low arch support, no wedges, hard damping (Con2). Maximum pronation velocity was higher when running in NS than in Con1 (p = 0.03) and when running at higher speeds (p < 0.01). Subjects showed increased ROM when wearing NS compared to Con1 (p < 0.01) or Con2 (p = 0.04) and at higher speeds (p < 0.01). As shoe variations and running speed led to changed kinematics, these parameters should be considered when investigating biomechanical parameters.